Analisis Rendahnya Kemampuan Literasi dan Numerasi SD Inpres Bontote’ne Pattarungan Bajeng Barat - Nanda Mayla Faizha Nur; Muhammad Syukur (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Inpres Bonto'tene Elementary School, to be precise in Pattarungan Village, West Bajeng District, Gowa Regency, the low literacy and numeracy skills of these students occur due to a lack of attention and teaching from their parents and some of their teachers. The method used in this research is a qualitative method which will produce research that is accurate and factual. The type of approach taken is a descriptive approach that describes a situation or phenomenon more accurately. Methods of data collection is done through interviews, direct observation and documentation. The total number of students is 108 people and the number of classes is only 6, there are some students who are not yet able to do calculations, multiplication and division, while some of the grade levels are still unable to read and you can see which ones are still spelling and not fluent. With the Teaching Campus activities held by the Ministry of Education and Culture, it is hoped that it will be able to create and improve the National Literacy Movement in schools which will then provide interesting experiences for students and students at school.